Conceptual analysis of e-recruitment: The role of web-site usability and organizational attraction of personnel in Nigeria - Musalli, Naziru Mohammed; Harun, Azhar; Zainuddin, Ruslan (2015)
E-recruitment is interchangeably used as the practice of recruitment by means of cyber space. E-recruitment has been described as online recruitment, internet recruiting or cyber space recruiting using electronic web-based practice to advertise job vacancies online. As a result of rapid increased of technology advancement, the level of utilizing internet and electronic mails in conducting business activities in organizations had evident globally.The aims of this study are to examine the importance of e-recruitment in facilitating organizational process of selecting quality and competence employees.The impact of globalization on today’s tight and competitive labour market, available vacancies most be fill with qualified candidates as a major roles played by human resource managers.In the same vein, organizations realised that proper management of men, money, method, machinery etc, resulted to higher degree of productivity when suitable qualified people are recruited. In view of the above discussion therefore, this study is carried out to investigate the problems and provide the possible solution to organization on how to attract large pools number of applicants in recruitment process.